MMP‐2 regulates Src activation via repression of the CHK/MATK tumor suppressor in osteosarcoma - Maybee, Deanna V.; Cromwell, Christopher R.; Hubbard, Basil P.; Ali, Mohammad A. M. (Cancer reports, 2024)
Background Doxorubicin, a first‐line anticancer drug for osteosarcoma treatment, has been the subject of recent research exploring the mechanisms behind its chemoresistance and its ability to enhance cell migration at sublethal concentrations. Matrix metalloproteinase‐2 (MMP‐2), a type IV collagenase and zinc‐dependent endopeptidase, is well‐known for degrading the extracellular matrix and promoting cancer metastasis. Our previous work demonstrated that nuclear MMP‐2 regulates ribosomal RNA transcription via histone clipping, thereby controlling gene expression. Additionally, MMP‐2 activity is regulated by the non‐receptor tyrosine kinase and oncogene, Src, which plays a crucial role in cell adhesion, invasion, and metastasis. Src kinase is primarily regulated by two endogenous inhibitors: C‐terminal Src kinase (Csk) and Csk homologous kinase (CHK/MATK). Aim In this study, we reveal that the MMP‐2 gene acts as an upstream regulator of Src kinase activity by suppressing its endogenous inhibitor, CHK/MATK, in osteosarcoma cells. Methods and Results We show that enhanced osteosarcoma cell migration which is induced by sublethal concentrations of doxorubicin can be overcome by inactivating the MMP‐2 gene or overexpressing CHK/MATK. Our findings highlight the MMP‐2 gene as a promising additional target for combating cancer cell migration and metastasis. This is due to its role in suppressing on the gene and protein expression of the tumor suppressor CHK/MATK in osteosarcoma. Conclusion By targeting the MMP‐2 gene, we can potentially enhance the effectiveness of doxorubicin treatment and reduce chemoresistance in osteosarcoma.